LESSONS FROM THE ESTABLISHED STATUS EPILEPTICUS TREATMENT TRIAL - Cock, Hannah R. (Epilepsy Behav, 2019)
Convulsive status epilepticus is a relatively common emergency condition affecting individuals of all ages. The primary goal of treatment is prompt termination of seizures. Where first line treatment with benzodiazepine has failed to achieve this, a condition known as established status epilepticus, there is uncertainty about which agent to use next. The Established Status Epilepticus Treatment Trial is a 3 arm (valproate, fosphenytoin, levetiracetam), phase III, double blind randomised comparative effectiveness study in patients aged 2 years and above with established convulsive status epilepticus. Enrollment was completed in January 2019, and the results are expected later this year. We discuss lessons learnt during the conduct of the study in relation to: ethical considerations; trial design and practical implementation in emergency settings; including paediatric and adult populations; quality assurance and outcome determination where treating emergency clinicians may lack specialist expertise. We consider ESETT is already informing both clinical practice and future trial design.